Prevalence of Anaplasma phagocytophilum in humans in Belgium for the period 2013–2016. Issue 4 (4th July 2019) - Hing, Mony; Van Den Bossche, Dorien; Lernout, Tinne; Cochez, Christel; Pirnay, Jean-Paul; Heuninckx, Walter
ABSTRACT: Ticks are vectors for a broad range of pathogens of medical and veterinary importance, such as Borrelia spp., Babesia spp., Anaplasma spp., Rickettsia spp., Bartonella spp. and the tick-borne encephalitis virus. The Gram-negative bacterium Anaplasma phagocytophilum is present worldwide, including Belgium where numerous patients were shown to harbour antibodies against this pathogen as recorded by the Belgian National Reference Center (NRC) for Anaplasma. The clinical presentation of human granulocytic anaplasmosis is an acute, febrile, nonspecific, flu-like illness. Leukopenia, thrombocytopenia and increased hepatic transaminase activities are commonly present early in the disease. Diagnosis early in the course of infection relies on the detection of antibodies or of the bacterium in the blood, as is performed at the NRC for Anaplasma, part of the Clinical Laboratory of the Queen Astrid Military Hospital in Brussels, Belgium. In this article, we discuss diagnostic test results as well as recent clinical and demographic characteristics of patients whose samples were analyzed by the NRC for Anaplasma in a four-year period (2013–2016).